PENINGKATAN HASIL BELAJAR PKN SISWA KELAS 2 MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE BERBANTUAN FLASH CARD - Sunusi, Nur Fadhila; Irfan, Muh; Nurhayati, Nurhayati (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Based on the results of observations made by researchers at SD Inpres Gontang, Makassar City, the problem that arises is the lack of interest of students in participating in the learning process because the teacher's way of teaching is still using conventional methods so that students' interest in participating in the learning process decreases. This research was carried out in class 2 with the spiral model PTK research proposed by C. Kemmis and Mc. Taggart. The research used 2 cycles, namely cycles 1 and 2 which consisted of planning, action and observation, and reflection stages. Research data was obtained from test results and analyzed using comparative descriptive techniques by comparing the learning outcomes of Civics subjects in 2 cycles based on completeness of learning outcomes, namely ≥ 65. The research results showed an increase in Civics learning outcomes which can be seen in the value of Civics learning outcomes based on completeness. learning, namely cycle I amounted to 66.77% and cycle II amounted to 87%. Based on the results of this comparison, this research has succeeded in improving student learning outcomes in Civics subjects.